Hedges used in Kurdish Political Discourse - Rafiq Moheddin , Kurdistan; Abdulkareem Sherwani, Kawa (International Journal of Psychosocial Rehabilitation, 2019)
This paper works within the framework of E.F. Prince, J. Frader, and C.Bosk theory (1982) and employs qualitative and quantitative methods. It analyzes President Masoud Barzani’s speeches. In addition, this study aims at analyzing the hedges from the pragmatic perspective and focuses on their functions rather than forms. Hedges are specific expressions such as ‘I think’, ‘a sort of’,’ entirely’, etc., which may be employed by interlocutors as significant strategies to make things fuzzier or less fuzzy. Moreover, attention has also been given to investigate and examine the frequency of occurrence of hedges in Kurdish political speech. This paper also tries to highlight how in Kurdish presidential speeches hedges have been employed to indicate a lack of complete commitment to the truth or falsity of the proposition, to communicate messages more precisely, to soften the impact of an utterance, or to convey vagueness purposely to reduce the riskiness of face-saving threats.